Study of the Effect of Family Communication and Therapeutic Communication on Anxiety ODHA - Azizah Des Derivanti; Maulina Pia Wulandari; Antoni Antoni (Sekolah Pascasarjana Universitas Brawijaya, 2017)
The majority of people living with HIV/AIDS are in six districts: Gondanglegi, Dampit, Sumberpucung, Sumbermanjing Wetan, Kepanjen and Turen (WHO, 2016). People living with HIV/AIDS have an anxiety in their mind, fearless, and increase imun. Anxiety is a form of unpleasant emotion, characterized by terms like concerns, concerns, and fears that are sometimes experienced in different levels. Resercher use Beck Anxiety Inventory to masure their apprehention in their self. One way to overcome anxiety is by doing therapy or counseling. Therapy or counseling is a process of providing information through systematic interpersonal communication. In this resech, interpersonal communication is family communication (FACE IV) and therapeutic communication (Tcomm-skill GP). There are 3 formulation of the problems, Is there any Â corelation of family communication as support system to the anxiety? Â Is there any therapeutic communication relationship between patient (ODHA) therapist to handle the anxiety of ODHA? Is there a common role to reduce anxiety?. The purpose of this study is to know the correlation of the role of family communication to anxiety, to know the correlation of therapeutic communication role to anxiety and to know the role of together to anxiety. Â Researcher using kuantitatif simple regresion to see how corelation they are.